PENINGKATAN MINAT BACA SISWA MELALUI POJOK BACA DI MIN 7 MAGELANG - Marista Putri Ariftina; Dahlia Dahlia (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
The aim of this research is to explain how to increase reading interest in the management of education based on resources by involving the management of the learning environment and resources (books, facilities, and time) to create an atmosphere that supports reading activities. This type of research is a case study with an ABCD approach method. This method is intended for local residents to first understand, inventory, and optimize the important assets available around them. The subjects of this research are students or learners. The results of this study indicate that to enhance students' interest in reading, it is necessary to utilize the school library's collection of books that had previously been underused. Initial observations showed that students' reading interest was low and they were not engaged in literacy activities. This program is designed as a comfortable and interactive reading space that supports literacy activities in the classroom through an Appreciative Inquiry approach (Discovery, Dream, Define, Destiny). The results of the implementation show that students are more engaged in reading and all parties responsible in the school are more actively involved. The reading corner program has the potential to function as a sustainable literacy center and help create a reading culture in the school environment.